Selection of forging process for compressor disc for aero engine using finite element analysis. (2022) - Jayanthi, A.; Anilkumar, M.; Ravisankar, B.
Abstract: Compressor discs for aero-engine applications are very critical in nature with respect to application and near alpha Ti alloys are used for this application due to its high specific strength combined with good corrosion resistance, fracture toughness, superior high temperature properties. Its processing technique is also highly complex and in open literatures is hardly available. In this paper, forging process sequence for manufacturing the compressor disc has been optimized using finite element analysis. Simulation results are analyzed for load, temperature, strain and material flow behavior. Based on the simulation studies, upsetting in two stages from cylindrical billet using hydraulic press and die forging in pneumatic hammer is recommended. .